Peran Hubungan Masyarakat Yayasan Kursus Bahasa Inggris Best Binjai Dalam Pengelolaan Isu Dan Pembentukan Citra Positif - Nazwa Fazriana Kalicha; Sigit Hardiyanto (Universitas Muhammadiyah Sumatera Utara, 2026)
This study is motivated by the intense competition among both local and online English course institutions, which demands a strategic public relations role in managing issues and building a positive image. The BEST Binjai English Course Foundation faces external challenges such as perceptions of value for money and the need for responsive communication. A descriptive qualitative approach was employed. Data were collected through semi-structured interviews, field observations, and documentation studies. Nine informants were selected using purposive sampling, consisting of public relations staff, foundation employees, instructors, and parents. Data analysis followed Creswell’s model, including data reduction, data display, and conclusion drawing. Findings show that PR manages issues through systematic complaint handling, internal coordination, and responsive communication. PR roles reflect Cutlip’s four functions, communication technician, expert prescriber, communication facilitator, and problem-solving facilitator. Positive image building is achieved through excellent service, need-based programs (private classes, integrated curriculum, parent reports), and optimized interpersonal, group, and social media. The strategy’s effectiveness is evidenced by parent testimonials citing ease of communication, quick responsiveness, and significant improvement in their children’s English skills.This study is motivated by the intense competition among both local and online English course institutions, which demands a strategic public relations role in managing issues and building a positive image. The BEST Binjai English Course Foundation faces external challenges such as perceptions of value for money and the need for responsive communication. A descriptive qualitative approach was employed. Data were collected through semi-structured interviews, field observations, and documentation studies. Nine informants were selected using purposive sampling, consisting of public relations staff, foundation employees, instructors, and parents. Data analysis followed Creswell’s model, including data reduction, data display, and conclusion drawing. Findings show that PR manages issues through systematic complaint handling, internal coordination, and responsive communication. PR roles reflect Cutlip’s four functions, communication technician, expert prescriber, communication facilitator, and problem-solving facilitator. Positive image building is achieved through excellent service, need-based programs (private classes, integrated curriculum, parent reports), and optimized interpersonal, group, and social media. The strategy’s effectiveness is evidenced by parent testimonials citing ease of communication, quick responsiveness, and significant improvement in their children’s English skills